Documenting Behavioral Health Needs in an Urban Setting - Hudson, Darrell; McCrary, Stacey; Murugan, Vithya; Gerassi, Lara; Proctor, Enola K. (Frontiers in Public Health, 2021)
Most local communities lack the capacity to conduct behavioral health needs assessments. The purpose of this paper is to describe a mixed-methods approach to estimate the behavioral health needs in St. Louis, MO. Data were drawn from multiple sources including local and state government prevalence estimates, medical records and key informant interviews. The most prevalent behavioral conditions were depression, alcohol, and drug abuse. Priority populations were residents with co-occurring disorders, youth transitioning into the adult behavioral system and homeless individuals with behavioral health needs. Treatment rates for behavioral health conditions were low, relative to identified needs. There are significant provider shortages and high staff turnover, which extend wait times, diminish the quality of care and contribute to the use of emergency departments for behavioral health care. The data and methods described in this paper could be helpful to other municipalities that are looking to conduct behavioral health needs assessments.